Analyzing radiation defects in photonic integrated circuits - Mienta, Kevin, author; Nikdast, Mahdi, advisor; Ray, Biswajit, advisor; Mooney, Michael, committee member (Colorado State University. Libraries, 2025)
This thesis aims to address the challenges in analyzing the performance of silicon photonic integrated circuits under radiation effects. Silicon photonic integrated circuits (PICs) are increasingly being explored for next-generation optical communication systems in both near-Earth and deep-space missions. This growing interest stems from the rising demand for high-throughput data links—potentially reaching terabit-per-second rates—alongside the pressing need to reduce size, weight, power consumption, and cost (SWaP-C). As missions push further into harsh space environments, it becomes critical to evaluate the impact of space radiation on the performance and reliability of PICs. Physically developing and analyzing PIC performance in radiation-harsh environments is a long and expensive process. A radiation-aware design-space exploration and simulation framework, called RADPIC, was developed to analyze the performance of PICs under radiation effects. RADPIC consists of optical and electrical analyses and simulations that consider the impact of total ionizing dose (TID) on silicon-on-insulator (SOI) based PICs. As a case study, the performance (e.g., frequency response, extinction ratio, Quality-factor) of a microring resonator modulator (MRM) was analyzed under radiation exposure. The results are compared with previously reported experimental data and demonstrate good agreement. RADPIC lays the foundation for developing radiation digital twin models, enabling enhanced performance and radiation hardness of PICs for space missions.